Report on Nutrition-Sensitive Deltaic Agri-food Projects/Systems on Nutrition and Health - HQ, WorldFish (WorldFish, 2024)
This report examines nutrition-sensitive interventions (NSIs), and agri-food systems positioned in the CGIAR Initiative on Asian Mega-Deltas (AMD), specifically focusing on Bangladesh, Cambodia, and Vietnam. These countries face distinct socio-economic and environmental challenges, making them pivotal in addressing food and nutrition security (FNS). Despite progress in agricultural productivity, economic growth, and nutrition and health, these countries are also faced with the triple burden of malnutrition, encompassing undernutrition, micronutrient deficiencies, and rising obesity rates. Limited access to diverse and nutrient-rich foods, compounded by climate variability and environmental degradation, exacerbates these nutritional issues. The report utilized a scoping desk review as its primary methodology. This involved qualitative data collection through an extensive review of documents related to NSIs and agri-food systems in the deltaic regions of Bangladesh, Cambodia, and Vietnam. The study analyzed reports, policy documents, and literature provided by AMD and WorldFish, covering implemented projects and national strategies. Key findings highlight persistent nutritional issues like stunting, anemia, and micronutrient deficiencies, with all three countries falling short of global nutrition targets. Despite increases in food production, access to diverse, nutritious diets remains limited, particularly among vulnerable groups.